Z dziejów budowy pałacu Przebendowskich w Warszawie - Sito, Jakub (Sztuka i Kultura, 2021)
The Grand Treasurer of the Crown Jan Jerzy Przebendowski (1639–1729), henchman of August II at that time holding one of the most important and lucrative central offices, has been of interest to the historians for many years. Also his two palatial homes – in Lezienko near Gdańsk and in Warsaw in Bielańska street – have been of interest among researchers. A sumptuous palace in Bielańska street – one of the leading examples of the capital city’s palace architecture of the late Baroque – became, among other mentions, the subject matter of Anna Saratowicz’s monograph. That multi-level building, representing the type of a detached mansion with single-axis bedchambers in the corners of its four-sided body was characterized by two stout two-floor solid blocks connected to each other and built into the body on its main axis, among others the front oval shape protruding into the honorary courtyard – perhaps the most characteristic motif of the Warsaw mansion of the Grand Treasurer. So far, neither the circumstances of its foundation nor the designer or the contractor have been revealed, nothing is known of the building process or its cost. New light has been shed on building of the Warsaw palace by the so far unknown archive items preserved in the National Historic Archive of Belarus in Minsk and in the Archiwum Głowne Akt Dawnych (Central Archive of Historical Records) in Warsaw. The information from the above mentioned sources is in fact scarse, very fragmentary and significantly far from completeness, it does, however, enable a certain specification of the building process of the Warsaw palace of the Treasurer. The beginnings of its erection, certainly a few seasons long, can be dated to ca. 1720 or even earlier – at the end of the first decade of 18th century. However, the earliest archive information dates back to as late as 1724 and refers to the building of the picket fence closing the residence off from the side of the garden. In the following year 1725 side outbuildings were erected. The erection of the outbuildings and the fence constituted the final stage of the main building works. The works on the body of the palace – woodworking, roofing, stonemasonry, tinsmithy, glassworking and locksmithy, were noted down in the years 1725–1726, about the earlier basic bricklaying works – certainly lasting many seasons – there is no record at all. There is, however, some truly sensational information brought about by the contract for decorative moulding works signed in August 1727 by Jan Jerzy Przebendowski with famous Warsaw artists, the moulding artist Pietro Innocente Comparetti and the sculptor Johann George Plersch. Their task was to fill the triangular spaces above 27 windows of the first floor and to add mouldings to both facades – front and on the side of the garden. The original moulding ornamentation must have been removed during the 19th-century renovation so, unfortunately, we are not familiar with its appearance. Except for providing new findings in reference to the building history of the Warsaw home of the Przebendowski family, while also enriching the factual knowledge by the data from the second half of the 1720s and rectifying some of the presently existing opinion, the present article is clearly far from exhausting the issue of the erection of the palace in Bielańska street. It can be suspected that the National Historic Archive of Belarus in Minsk, in its Radziwiłł fond, preserves more so far unrecognized archive items connected to the Przebendowski family and their Warsaw mansion.